Indirect rule the making of US international hierarchy - Lake, David A. 1956- (Cornell University Press, 2024)
"Indirect rule has long characterized interstate relationships and remains a key mechanism of contemporary US foreign relations. In this book, David A. Lake examines when and why it is pursued over direct or domestic rule."--
Includes bibliographical references and index
Keywords: Hierarchie; Internationale Politik; Hegemonie; Internationales politisches System; USA; 21. Jahrhundert (2000 bis 2100 n. Chr.); 21st century; World politics; Power (Social sciences) / History; Dependency / History; Amerikanische Geschichte; Colonialism & imperialism; Diplomacy; Diplomatie; HISTORY / United States / 21st Century; History of the Americas; Kolonialismus und Imperialismus; POL047000; POLITICAL SCIENCE / International Relations / Diplomacy; Politics & government; Politik und Staat; United States / Foreign relations / Philosophy; Vereinigte Staaten von Amerika, USA